Answer:
-12x + 4
Step-by-step explanation:
(6x - 8 - 2x) - (12x - 7) - (4x - 5)
The subtraction sign before the parenthesis is basically multiplying by -1, so the subtraction signs in the parenthesis have to change to addition. After that, you can remove the parenthesis.
6x - 8 - 2x - 12x + 7 - 4x + 5
Simplified = -12x + 4
Answer:
3x - y = -3
Step-by-step explanation:
divide everything by 4, the greatest common factor. That's all you need to do.
D because some of the inputs have the same output therefor it is not a function
Answer:
y = 2x - 7
Step-by-step explanation:
The question is asking for slope-intercept form, y = mx + a.
Given:
(1, -5) and (9, 11)
Find the slope (m) between the two points:
m = (y2 - y1) / (x2 - x1)
x1 = 1
x2 = 9
y1 = -5
y2 = 11
m = ( 11 - (-5) )/(9 - 1)
= 16/8
m = 2
y = 2x + a
Use one of the two points to find a (I will use (1, -5)):
-5 = 2(1) + a
-5 = 2 + a
-7 = a
a = -7
y = 2x + (-7)
y = 2x - 7
Answer:
Step-by-step explanation:
<u>Subtract the values:</u>
- 19 1/12 - 8 5/12 =
- 18 13/12 - 8 5/12 =
- 18 - 8 + 13/12 - 5/12 =
- 10 + 8/12 =
- 10 8/12 =
- 10 2/3 in